The Structure of Macrozoobenthos Community in the Intertidal Zone of Api-Api Village Waters, Bandar Laksamana District, Bengkalis - Sari, Nova Iman; Nasution, Syafruddin; Efriyeldi, Efriyeldi (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2021)
This research aims to analyze the structure of macrozoobenthos community in the intertidal zone of Api-Api Village waters, Bandar Laksamana District, Bengkalis regency. There were 5 subzones determined as the observation areas. Each subzone consists of 5 subplots which taken parallel to the coast with a distance of 10 meters from each subplot. The types of macrozoobenthos found consisted of 4 classes, 19 families, and 23 species. The diversity index for each subzone ranged from 2.72 to 3.55, species uniformity index ranged from 0.78-0.91 and dominance index ranged from 0.11-0.19, with the criteria of a uniform distribution pattern. The highest macrozoobenthos density was in subzone 1 with a total density of 19.6 ind/m2, while the lowest was in subzone 4 with a total density of 10.6 ind/m2. The result of statistical tests using Analysis of Variance (ANOVA) at a confidence interval of 95% (ɑ = 0.05), showed that macrozoobenthos density in subzone 1,2,3,4 and 5 was not significant in different (P = 0.824), which means that there was no real different density that five subzones